Spillovers to Emerging Equity Markets : An Econometric Assessment - Sun, Tao (IMF Working Papers; Working Paper, 2009)
This paper shows that emerging market equity prices are influenced by growing global factors, and therefore global factors constitute a significant channel for spillovers when the international economic environment changes. Strengthening their resilience to equity price declines remains an important goal for emerging market economies.